Model Evaluasi Efektivitas Pengelolaan Sarana Dan Prasarana Pendidikan Di Madrasah : evaluasi - Anggi Febrina; Latifah Wulandari (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to identify an evaluation model for the effectiveness of educational facilities and infrastructure management in madrasahs. Facilities and infrastructure are essential components in supporting the quality of learning; however, their management often faces various challenges such as limited resources, the absence of standardized evaluation frameworks, and weak monitoring and reporting systems. The method used in this study is a literature review by examining various relevant scholarly sources such as books, journal articles, government regulations, and previous research reports. The collected data were analyzed using a descriptif-qualitative approach through conceptual synthesis, by comparing the characteristics of the CIPP model, discrevency evaluation, and the model based on the national education standars (SNP). The findings indicate that there are three relevant evaluation model approaches: the CIPP Model (Context, Input, Process, Product), the Discrepancy Evaluation Model, and the evaluation model based on the National Education Standards (SNP). Each of these models has its own characteristics and advantages in assessing the effectiveness of educational facilities and infrastructure management. By integrating these three approaches, madrasahs are expected to conduct evaluations systematically, measurably, and sustainably to improve the quality of educational services.